International Students and Higher Education: New Perspectives on Cultures and Communities - Montgomery, Catherine (Journal of International Students, 2013)
I was very pleased to be invited to be the guest editor for this issue of the Journal of International Students, not least because the journal presents cutting-edge research that is generating new perspectives in the field. The journal is filling a gap in the literature and its significance is drawing attention from other established journals such as the Journal of Studies in International Education (see the editorial of JSIE, 16 (1) 2013, p.3). One of the main strengths of the journal is its combination of contributions from established researchers and emergent researchers many of whom have experienced international mobility themselves and are undertaking doctoral studies in this field. Previous work has noted the under-exploited nature of research work carried out by international students and staff themselves and its potential in informing the field.